THE INTERPRETATION OF THE IMAGE OF OSIMA IN THE WORKS OF ABDUVALI QUTBIDDIN - Quljanova To‘lg‘anoy Shodiyor qizi (Journal Park Publishing, 2025)
In this article, the cycle of poems “Osima” by Abduvali Qutbiddin, a mature representative of contemporary literature, is subjected to analysis. The artistic-poetic, philosophical, and Sufi interpretations of the image of Osima are revealed. In addition, reflections are presented on the place and function of the image of Osima in the poet’s poetry.
Keywords: Osima, path, beloved, lover, truth, irfan, and Sufism.